Corporate governance and cross-listing: evidence from European companies. - Bauer, R; Wójcik, D; Clark, G (School of Geography and Environment (University of Oxford), 2004)
This paper documents the relationship between cross-listing and corporate governance of the largest European companies between 2000 and 2003. Companies with a U.S. cross-listing, and particularly those listed on a U.S. stock exchange had higher corporate governance ratings than companies without a U.S. cross-listing. Corporate governance advantage of the U.S. cross-listed firms holds if we control for the country of origin and other company characteristics, and it was more consistent in 2003 than in 2000, suggesting a possible impact of the Sarbanes-Oxley Act. The U.S. cross-listed firms had higher ratings not only in terms of disclosure but also in terms of board structure and functioning. In contrast, they had no advantage in terms of shareholders' rights and duties. The advantage of U.S. cross-listed firms can be traced back to at least a couple of years before the time of cross-listing, which leaves the question whether their superior corporate governance is the effect of U.S. cross-listing open. In contrast to the importance of cross-listing in the U.S., there is no significant relationship between corporate governance and cross-listing within Europe. Implications are drawn for the debate on bonding and the future of European stock markets.